Ultrasonographic and ecobiometric findings in the eyes of adult goats - Ribeiro, Alexandre Pinto [UNESP]; Santos, Nailson Lima [UNESP]; Silva, Victor Costa e [UNESP]; Campos, Andressa Fernanda [UNESP]; Teixeira, Izabelle Auxiliadora Molina de Almeida [UNESP]; Laus, José Luiz [UNESP] (Universidade Federal de Santa Maria (UFSM), 2010)
Conhecer o aspecto e as dimensões de olhos de cabras facilita o uso da ultrassonografia na avaliação de doenças oculares. O objetivo do presente trabalho foi o de avaliar os achados ultrassonográficos e ecobiométricos em olhos de cabras adultas. Ultrassonogramas nos modos A e B foram realizados em 30 caprinos adultos (60 olhos) (n=15 fêmeas intactas e n=15 machos castrados). O exame ultrassonográfico foi realizado após a instilação de colírio anestésico. Gel a base de água foi utilizado sobre o transdutor de 20 MHz posicionado-o de forma longitudinasobre a córneal, até que imagens no modo B estivessem de acordo com os ecos gerados pelo modo A. Utilizou-se análise estatística para se comparar os achados ecobiométricos entre os sexos (p<0,05). As médias com seus respectivos desvios padrões das estruturas oculares em machos e fêmeas foram, respectivamente, 3,46±0,55, 3,33±0,46mm (profundidade da câmara anterior); 8,60±0,34, 8,65±0,39mm (espessura da lente); 11,34±0,61, 11,39±0,66mm (profundidade da câmara vítrea) e 23,43±0,92, 23,39±0.86mm (comprimento axial do bulbo ocular). Não foi observada diferença significativa entre os olhos direito e esquerdo, assim como entre machos e fêmeas (p>0,05). O aspecto ultrassonográfico de olhos de cabras se assemelha com o de outras espécies domésticas e silvestres.

The knowledge of the normal appearance and ocular dimensions of goat eyes facilitates the use of ultrasonography in the evaluation of ocular disease. The objective of the present study was to determine ultrasonographic and ecobiometric findings in the eyes of adult goats. B- and A-mode ultrasonography was performed in 30 healthy adult goats (60 eyes) (n=5 intact females and n=15 castrated males). Ultrasonography was performed after instillation of a topical anesthetic. Lubricating jelly was placed on the 20MHz transducer tip as a stand-off pad. The transducer was placed in a longitudinal position until optimal B-scan images, according to echoes of the A-mode images, were obtained. Statistical analysis was carried out to compare the ecobiometric readings among genders (P<0.05). Means and standard deviations of the ocular structures for male and female goats, respectively, were, 3.46±0.55, 3.33±0.46mm (anterior chamber depth); 8.60±0.34, 8.65±0.39mm (lens thickness); 11.34±0.61, 11.39±0.66mm (vitreous chamber depth); and 23.43±0.92, 23.39±0.86mm (axial globe length). Ocular measurements between right and left eyes, as well as between males and females were not significantly different (P>0.05). The ultrasonographic appearances of goat eyes were very similar to those of other domestic and wild species.
Achados ultrasonográficos e ecobiométricos em olhos de cabras adultas
Keywords: Capra hircus; ultrassonografia ocular; ecobiometria; Capra hircus; ocular ultrasonography; ecobiometry